CONTROL OF POLITICAL POWER AND ADMINISTRATIVE DISHONESTY: AN ANALYSIS OF THE NEED TO PROVE DECEIT IN ADMINISTRATIVE IMPROBITY ACTIONS BASED ON THE WORK OF KARL LOEWENSTEIN (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article analyzes the requirement of proof of intent to configure an act of administrative improbity from the analysis of Karl Loewenstein's book "Political Power and the Governmental Process". One of the most relevant changes in the administrative improbity law (law n. 8,429/92) promoted by law n. 14.230/21 is the need to prove the intentional subjective element inherent in the conduct of the agent or the individual so that a certain act that violates administrative morality can be considered unprofessional. In this sense, Loewenstein's work will support the answer to the following question: does the need to prove intent in acts of administrative improbity represent a weakening of the control of political power? In order to answer the question, considerations will be made on the subjective element in administrative improbity and on the teachings of Karl Loewenstein. Conclusively, it will be verified that, contrary to what a priori may seem, the aforementioned legislative innovation is the consecration of the ideal of control of political power and is directly related to the substantial content of the Democratic State of Law.